Analisa Kedudukan Pemberian Keterangan Ahli Terhadap Proses Ilmu Forensik dan Tinjauannya Menurut Hukum Islam - Amara Aurelia; Ferryal Basbeth; Firman Arifandi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Forensic science is needed in the trial process, one of which is to assist judges in knowing a fact. The implementation of upholding justice requires expert information relating to legal functions where this expert's information will become a valid piece of evidence in accordance with Article 184 of the Criminal Procedure Code. Expert information is what is stated by an expert in court, either in oral or written form. According to Islamic law, the testimony of a doctor can be used as evidence. This study uses a normative juridical method. The search used in this study was Google Scholar, the search application Publish or Perish, and Neliti. This study found that expert testimony is needed in the trial process as evidence and gives the judge confidence in making a decision. The expert's statement is free and unbound, but the judge still has to consider the expert's statement if there is compatibility with other evidence. The position of expert testimony is as valid evidence in accordance with Article 184 of the Criminal Procedure Code which will help clarify a case in court.